Inflammation in Coronary Atherosclerosis: Insights into Pathogenesis and Therapeutic Potential of Anti-Inflammatory Drugs - Clara Salles Figueiredo; Elias Soares Roseira; Tainá Teixeira Viana; Marcelo Augusto Duarte Silveira; Rodrigo Morel Vieira de Melo; Miguel Godeiro Fernandez; Livia Maria Goes Lemos; Luiz Carlos Santana Passos (MDPI AG, 2023)
Atherosclerosis is a lipid-driven immune-inflammatory disease that affects the arteries, leading to multifocal plaque development. The inflammatory process involves the activation of immune cells and various inflammatory pathways. Anti-inflammatory drugs have been shown to be effective in reducing cardiovascular events in individuals with coronary disease. However, their use is still limited due to concerns about long-term follow-up, cost-effectiveness, adverse effects, and the identification of the ideal patient profile to obtain maximum benefits. This review aims to improve the understanding of inflammation in coronary atherosclerosis and explore potential therapeutic interventions, encompassing both traditional and non-traditional anti-inflammatory approaches. By addressing these concepts, we seek to contribute to the advancement of knowledge about this type of treatment for coronary artery disease.